Muddy puddles – the microbiology of puddles located outside tertiary university teaching hospitals. (1st April 2018) - Furukawa, M.; McCaughan, J.; Stirling, J.; Millar, B.C.; Bell, J.; Goldsmith, C.E.; Reid, A.; Misawa, N.; Moore, J.E.
Abstract: In the British Isles, the frequency of rain results in the formation of puddles on footpaths and roads in/around hospitals. No data are available demonstrating the microbiological composition of such puddles and therefore a study was undertaken to examine the microbiology of puddles in the grounds of two tertiary university‐teaching hospitals (18 sites) and compared with control puddles from non‐hospital rural environments (eight sites), estimating (i) total viable count; (ii) identification of organisms in puddles; (iii) enumeration of Escherichia coli : (iv) detection of Extended Spectrum β ‐Lactamase producing organisms and (v) direct antimicrobial susceptibility testing. A mean count of 2·3 × 10 3 CFU per ml and 1·0 × 10 9 CFU per ml was obtained for hospital and non‐hospital puddles respectively. Isolates ( n = 77; 54 hospital and 23 non‐hospital) were isolated comprising of 23 species among 17 genera (hospital sites), where the majority (10/16; 62·5%) of genera identified were Gram‐negative approximately, a fifth (20·6%) were shared by hospital and non‐hospital rural samples. Escherichia coli was detected in half of the hospital puddles and under‐half (37·5%) of the rural puddles extended spectrum β ‐lactamase organisms were not detected in any samples examined. Rainwater puddles from the hospital and non‐hospital environments contain a diverse range of bacteria, which are capable of causing infections. Significance and Impact of the Study: This study demonstrated the presence of a wide diversity of bacterial taxa associated with rainwater puddles around hospitals, many of which are capable of causing human disease. Of clinical significance is the presence of Pseudomonas aeruginosa isolated from a hospital puddle, particularly for patients with cystic fibrosis. The presence of potentially disease‐causing bacteria in puddles in and around hospitals identifies a new potential environmental reservoir of bacteria. Furthermore work is now needed to define their potential of entering or exiting hospital wards by contaminated footwear.